Practical training report: MADA Rice Training Center (MRTC) / Wardah Zainon - Zainon, Wardah (University Technology MARA Sarawak, 2016)
MADA Rice Training Center known as MRTC is one of the branches that handle the intake of practical students. It is a training section for rice production where they offer program Sijil Kemahiran Malaysia (SKM) for production of rice. Besides, the activities and main function of MUDA Agriculture Development Authority (MADA) is relating to rice industry. There are three level of program that has been offered which is Level 1: Pekerja Am Ladang (6 months), Level 2: Pekerja Kanan Ladang Padi (6 months) and Level 3: Penyelia Ladang Padi (12 months). Here the trainee has been placed for administrative work and also some outdoor activities such as visit their field work. There is no strictly requirement to attract the young interest to involve in agricultural sector.